A New Class of Contraction in b-Metric Spaces and Applications - Preeti Kaushik; Sanjay Kumar; Kenan Tas (Abstract and Applied Analysis)
A novel class of α-β-contraction for a pair of mappings is introduced in the setting of b-metric spaces. Existence and uniqueness of coincidence and common fixed points for such kind of mappings are investigated. Results are supported with relevant examples. At the end, results are applied to find the solution of an integral equation.